NOTARY AUTHORITY IN MAKING INHERITANCE DISTRIBUTION DEED FOR INHERITANCE IN THE FORM OF LAND - Dinda Namira Anindya; F.X Arsin Lukman (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
One of the authorities of the Notary as mandated in the Undang-undang Jabatan Notaris (UUJN) is the making of authentic deeds related to land. In line with this provision, the Government Regulation on Land Registration stipulates that one of the deeds required in the event of a transfer of land rights due to inheritance is a deed of inheritance division which can take the form of a notarial deed or an underhand deed. However, in addition to notaries, there are other officials authorized to make deeds in the land sector, namely Pejabat Pembuata Akta Tanah (PPAT). The purpose of this research is to analyze the authority of Notary in making deeds related to land including inheritance division deeds and the comparison between inheritance division deeds which are notarial deeds and joint rights division deeds which are PPAT deeds. This research is juridical-normative research, namely research based on legal norms contained in applicable laws and regulations. The result of this research is that the authority of Notary to make deeds in the land sector, including the deed of inheritance division on inherited land does not conflict with the authority of PPAT, and the deed of inheritance division and the deed of division of joint rights are two different deeds, both in terms of form and material.